PHYSICAL MODEL TEST OF NATURAL COASTAL PROTECTION SYSTEM : A CASE STUDY OF THE EFFECTS OF WEIGHT AND STRUCTURE SLOPE OF GEOBAG TO WAVE TRANSMISSSION OF GEOBAG STRUCTURE - Luqman Al Hakim, Muhammad
Erosions is one of the serious problems that occur in coastal areas. One of the methods of erosion control is the use of natural coastal protection structure that is mangrove. But in the process of planting and growing of mangrove seedlings, which needs to be considered is environmental conditions for mangrove to grow well. Therefore it is necessary to protect the seeds of mangrove that is being grown. One of the most effective, easy to make, and modelable physically, is the geobag structure. In this final project, physical model test of natural coastal protection system is consisted of permanent structure that is mangrove and temporary structure that is geobag structure. The modelling scenario is done by varying the weight and slope structure of geobag used and the variation of wave parameters formed by the wave maker. The problem analysed is limited to the effects of weight and slope structure of geobag to wave transmission of geobag structure. The standard used in this physical model test is “Physical Models and Laboratory Techniques in Coastal Engineering (Hughes, 1993)”. The scale used in this project is 1 : 10. The geobag model used 3 weight variation, 0.5 kg, 1 kg, and 2 kg. Geobag models are assembled into structure with lower width 140 cm, upper width 20 cm., and height 40 cm for structure slope 1 : 1.5 scenario and lower width 180 cm, upper width 20 cm, and height 40 cm for structure slope 1 : 2 scenario. Wave periods used are 4.7 s, 3.5 s, and 2.8 s. the wave height used is in the range of 4 – 14.5 cm. The number of scenario tested in this physical model test is 6, but only 4 is analyed in this final project regarding wave transmission in geobag structure. The result shows that the weight of geobag give significant effect to the wave transmission of geobag structure, with the heavier geobag resulted in smaller kt. The average value of kt for scenarios with geobag 0.5 kg, 1 kg, and 2 kg respectively are 0.69, 0.60, and 0.42. The slope of geobag structure only give effect on certain wave condition. The average value of kt for scenarios with geobag 2 kg slope 1 : 1.5 and geobag 2 kg slope 1 : 1 : 2 respectively are 0.42 and 0.49. The slope 1 : 1.5 scenario gives a smaller kt values for 5 out of 9 wave variations tested compared to the slope 1 : 2 scenario.